DNA methylation of claudin-6 promotes breast cancer cell migration and invasion by recruiting MeCP2 and deacetylating H3Ac and H4Ac. Issue 1 (December 2016) - Liu, Yafang; Jin, Xiangshu; Li, Yanru; Ruan, Yang; Lu, Yan; Yang, Minlan; Lin, Dongjing; Song, Peiye; Guo, Yantong; Zhao, Shuai; Dong, Bing; Xie, Yinping; et al.
Abstract Background Claudin-6 (CLDN6), a member of claudin transmembrane protein family, has recently been reported to be undetectable or at low levels in human breast cancer cell lines and tissues and plays a role in suppression of migration and invasion in breast cancer cells. In addition, it is reported that CLDN6 expression is regulated by DNA methylation in various human cancers and cell lines. However, it is unclear how DNA methylation regulates CLDN6 expression. Here we show the mechanism by which DNA methylation regulates CLDN6 expression in human breast cancer cell line MCF-7. Methods RT-PCR, Western blot and immunofluorescent staining were utilized to investigate CLDN6 expression in breast cancer tissues and MCF-7 cells. Methylation-Specific PCR (MSP) was applied to determine DNA methylation status in CLDN6 gene promoter region. Wound-healing assay and invasion assay were utilized to test mobility of MCF-7 cells treated with 5-aza-dC (DNA methyltransferase inhibitor). MeCP2 binding, H3Ac and H4Ac in CLDN6 promoter region were analyzed by ChIP assay. Nuclease accessibility assay was performed for analysis of the chromatin conformation of CLDN6 gene. To study the role of CLDN6 in malignant progression, we used RNAi to knockdown CLDN6 expression in MCF-7 cells treated with 5-aza-dC, and examined the mobility of MCF-7 cells by wound-healing assay and invasion assay. Results 5-aza-dC and TSA (histone deacetylase inhibitor) application induced CLDN6 expression in MCF-7 cells respectively and synergistically. 5-aza-dC treatment induced CLDN6 demethylation, inhibited MeCP2 binding to CLDN6 promoter and increased H3Ac and H4Ac in the promoter. In addition, TSA increased H4Ac, not H3Ac in the promoter. The chromatin structure of CLDN6 gene became looser than the control group after treating with 5-aza-dC in MCF-7 cells. 5-aza-dC up-regulated CLDN6 expression and suppressed migration and invasion in MCF-7 cells, whereas CLDN6 silence restored tumor malignance in MCF-7 cells. Conclusions DNA methylation down-regulates CLDN6 expression through MeCP2 binding to the CLDN6 promoter, deacetylating H3 and H4, and altering chromatin structure, consequently promoting migratory and invasive phenotype in MCF-7 cells.